Techno-Humanistic Paradigm in Physical Education: Integrating Love-Based Curriculum and Digital Technology in Islamic Schools - Sri Widaningsih; Erni Kusmiat; Deswita Supriyatni; Veny Juniarni Hardi; Ulfa Futri Hasyimiyah Qissa'Ali (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
The rapid integration of digital technology in physical education has transformed teaching and learning practices while simultaneously raising concerns regarding the dehumanization of educational interactions. This study investigates the implementation of the Techno-Humanistic Paradigm through the integration of a Love-Based Curriculum and digital technology in physical education learning at MTsN 1 Bandung Ciparay, Indonesia. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews with three physical education teachers, two school administrators, and twenty-four students, as well as document analysis. The data were analyzed using thematic analysis supported by source and method triangulation to ensure credibility and trustworthiness. The findings indicate that the Techno-Humanistic Paradigm is manifested through student-centered digital learning, compassion-oriented teacher–student interactions, reflective learning practices, and the incorporation of empathy, cooperation, sportsmanship, and respect into technology-enhanced physical education activities. Despite challenges related to maintaining interpersonal relationships, balancing technological efficiency with humanistic values, and disparities in digital literacy, the integration process generated positive outcomes, including increased student engagement, personalized learning experiences, improved digital competence, emotional awareness, collaboration skills, and character development. This study contributes to the literature by proposing the concept of Digital Compassion in Physical Education, a novel framework that integrates technological innovation with human dignity, empathy, and care. The framework offers an alternative model for developing holistic and value-based physical education practices in Islamic schools within the digital era.